2019
DOI: 10.3847/2041-8213/ab1f92
|View full text |Cite
|
Sign up to set email alerts
|

The Main Sequence at z ∼ 1.3 Contains a Sizable Fraction of Galaxies with Compact Star Formation Sizes: A New Population of Early Post-starbursts?

Abstract: ALMA measurements for 93 Herschel -selected galaxies at 1.1 z 1.7 in COSMOS reveal a sizable (> 29%) population with compact star formation (SF) sizes, lying on average > ×3.6 below the optical stellar mass (M )-size relation of disks. This sample widely spans the star-forming Main Sequence (MS), having 10 8 M 10 11.5 M and 20 SF R 680 M yr −1 . The 32 size measurements and 61 upper limits are measured on ALMA images that combine observations of CO(5-4), CO(4-3), CO(2-1) and λ obs ∼ 1.1−1.3 mm continuum, all t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
110
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(145 citation statements)
references
References 55 publications
31
110
3
Order By: Relevance
“…A.1 and A.2) also suggests the presence of compact or clumpy optical morphologies, which seem to be common in distant starforming and Herschel-selected galaxies. Consistent with these results, using ALMA observations Puglisi et al (2019) recently found that a significant fraction, that is, ∼50%, of their sample comprising 93 Herschel-selected galaxies at 1.1 ≤ z ≤ 1.7 and at the MS show a compact morphology. The authors interpret their sources as early post-starburst galaxies.…”
Section: Star Formation Enhancement and Gas Enrichmentsupporting
confidence: 62%
“…A.1 and A.2) also suggests the presence of compact or clumpy optical morphologies, which seem to be common in distant starforming and Herschel-selected galaxies. Consistent with these results, using ALMA observations Puglisi et al (2019) recently found that a significant fraction, that is, ∼50%, of their sample comprising 93 Herschel-selected galaxies at 1.1 ≤ z ≤ 1.7 and at the MS show a compact morphology. The authors interpret their sources as early post-starburst galaxies.…”
Section: Star Formation Enhancement and Gas Enrichmentsupporting
confidence: 62%
“…Di Matteo et al 2008;Hung et al 2013;Cibinel et al 2019), demonstrate that merging systems may lie on the main sequence. Puglisi et al (2019) find that up to 50% of the most massive galaxies on the MS at z ∼ 1.3 may have star formation driven by merging. Major merger activity may not enhance star formation rates at every stage of a merger (e.g.…”
Section: Main Sequence Of Galaxiesmentioning
confidence: 90%
“…Part of the data has been already used in previous works. In particular, Puglisi et al (2019) focused on the far-IR sizes of our sample and anticipated the blurred difference between upper MS and SB galaxies mentioned above, revealing a significant population of post-starburst galaxies on the main sequence. A more articulated analysis of the role of compactness on galaxy evolution is in preparation (Puglisi et al, in prep.).…”
Section: Introductionmentioning
confidence: 97%
“…The same definition of starbursts as galaxies deviating from the main sequence has been recently questioned with the advent of high spatial resolution measurements of their dust and gas emission. Compact galaxies with short depletion timescales typical of SBs are now routinely found on the MS, being possibly on their way to leave the sequence (Barro et al 2017a;Popping et al 2017;Elbaz et al 2018;Gómez-Guijarro et al 2019;Puglisi et al 2019;Jiménez-Andrade et al 2019); or galaxies moving within the MS scatter, due to mergers unable to efficiently boost the star formation (Fensch et al 2017) or owing to gravitational instabilities and gas radial redistribution (Tacchella et al 2016).…”
Section: Introductionmentioning
confidence: 99%